Expanding the phenotype of mutations in DICER1: mosaic missense mutations in the RNase IIIb domain of DICER1 cause GLOW syndrome. Issue 5 (27th March 2014) - Klein, Steven; Lee, Hane; Ghahremani, Shahnaz; Kempert, Pamela; Ischander, Mariam; Teitell, Michael A; Nelson, Stanley F; Martinez-Agosto, Julian A
Abstract : Background: Constitutional DICER1 mutations have been associated with pleuropulmonary blastoma, cystic nephroma, Sertoli-Leydig tumours and multinodular goitres, while somatic DICER1 mutations have been reported in additional tumour types. Here we report a novel syndrome termed GLOW, an acronym for its core phenotypic findings, which include G lobal developmental delay, L ung cysts, O vergrowth and W ilms tumour caused by mutations in the RNase IIIb domain of DICER1. Methods and results: We performed whole exome sequencing on peripheral mononuclear blood cells of an affected proband and identified a de novo missense mutation in the RNase IIIb domain of DICER1. We confirmed an additional de novo missense mutation in the same domain of an unrelated case by Sanger sequencing. These missense mutations in the RNase IIIb domain of DICER1 are suspected to affect one of four metal binding sites located within this domain. Pyrosequencing was used to determine the relative abundance of mutant alleles in various tissue types. The relative mutation abundance is highest in Wilms tumour and unaffected kidney samples when compared with blood, confirming that the mutation is mosaic. Finally, we performed bioinformatic analysis of microRNAs expressed in murine cells carrying specific Dicer1 RNase IIIb domain metal binding site-associated mutations. We have identified a subset of 3p microRNAs that are overexpressed whose target genes are over-represented in mTOR, MAPK and TGF-β signalling pathways. Conclusions: We propose that mutations affecting the metal binding sites of the DICER1 RNase IIIb domain alter the balance of 3p and 5p microRNAs leading to deregulation of these growth signalling pathways, causing a novel human overgrowth syndrome.